Craniofacial resection and its role in the management of sinonasal malignancies. Issue 9 (September 2012) - Taghi, Ali; Ali, Ahmed; Clarke, Peter
Sinonasal malignancy is rare, and its presentation is commonly late. There is a wide variety of pathologies with varying natural histories and survival rates. Anatomy of the skull base is extremely complex and tumors are closely related to orbits, frontal lobes and cavernous sinus. Anatomical detail and the late presentation render surgical management a challenging task. A thorough understanding of anatomy and pathology combined with modern neuroimaging and reliable reconstruction within a multidisciplinary team is imperative to carry out skull base surgery effectively. While endoscopic approaches are gaining credibility, clearly, it will be some time before meaningful comparisons with craniofacial resection can be made. Until then, craniofacial resection will remain the gold standard for managing the sinonasal malignancies of the anterior skull base, as it has proved to be safe and effective.